Games in Arabic for Early Childhood: A Literature Study - Rismayani, Rismayani; Siregar, Siti Mahpudzoh; Adelina, Hajijah; Lubis, Hilda Zahra (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
Language is a fundamental element in communication and child development, including in learning foreign languages such as Arabic. This study aims to explore the effectiveness of using game-based methods in teaching Arabic to early childhood learners. Games were chosen for their interactive, enjoyable nature and their ability to meet the psychological developmental needs of children. This research employs a qualitative approach with a literature study method, involving the analysis of various secondary sources, with eight journals analyzed in-depth. The findings reveal that games not only enhance linguistic skills (listening, speaking, reading, and writing) but also support children's social, cognitive, and motor development. The types of games analyzed include traditional games like kideng, picture guessing games, sequential picture games, spinning wheel games, card games, songs, and snake-and-ladder games. Additionally, games motivate children to learn actively, reduce boredom, and promote social engagement. In conclusion, a game-based approach is an effective and enjoyable method for teaching Arabic while simultaneously instilling Islamic values in early childhood. These findings provide new insights for educators in designing creative and adaptive Arabic learning tailored to children's needs.